PENERAPAN MEDIA FLIPBOOK DATA MAKANAN KHAS SEMARANG BERBASIS MODEL PROBLEM BASED LEARNING UPAYA PENINGKATAN MENGANALISIS DATA SISWA KELAS V SDN JATISARI SEMARANG - Icha Miranda Jelita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' low ability to analyze data is a problem that is often encountered in the learning process in elementary schools, including at SDN Jatisari. This affects students' understanding of the material presented, especially that involving data in the form of graphs, tables or diagrams. To overcome this problem, this research aims to explore the effectiveness of implementing flipbook learning media based on the Problem Based Learning (PBL) model in improving the ability to analyze data for grade 5 students. The research design used is a pretest-posttest one group design, by collecting data through pre-tests. -test and post-test to measure changes in students' data analysis skills. The research results showed that after implementing PBL-based flipbook media, there was a significant increase in students' ability to analyze data, which was reflected in the post-test scores which were higher than the pre-test. The discussion revealed that interactive flipbook media, with the theme of typical Semarang food, as well as the application of a PBL model based on contextual problem solving, succeeded in increasing student involvement and understanding. The conclusion of this research is that the application of PBL-based flipbook media is effective in improving students' ability to analyze data, as well as providing a more interesting and applicable learning experience.